(untitled) (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Cinnamic acid and derivatives are widely spread in plants. They are important intermediates in the synthesis of many aromatic compounds and are known to have diverse biological activities. Objectives: To synthesize, characterize and evaluate some cinnamic acid derivatives, for possible antimicrobial and anti-inflammatory activities. Material and methods: Different cinnamic acid derivatives were synthesized by Knoevenagel condensation reaction between malonic acid and various derivatives of benzaldehydes in the presence of pyridine and hydrochloric acid. The cinnamic acid epoxide was formed in the presence of hydrogen peroxide and KOH, while dihydro-cinnamic acid and paramethoxy-dihydro-cinnamic acids were formed by reducing cinnamic acid and paramthoxy-cinnamic acid respectively with raney nickel in the presence of 10% KOH. The final products were purified on column chromatography (CC), eluting with petroleum spirit/ethyl acetate. All the synthesized compounds were unequivocally characterized using the combination of UV-Vis Spectroscopy, infra-red (FTIR), 1H and 13C Nuclear Magnetic Resonance (NMR) spectroscopy. In-vivo anti-inflammatory activities of the synthesized compounds was investigated using egg albumin-induced paw oedema in rat; while antimicrobial activity was evaluated by agar diffusion method. Results: The compounds were obtained in high yield (30 – 97 %) and purity. 3,4-dioxomethylene cinnamic acid produced the highest (60.8%) and significant (p < 0.05) anti-inflammatory effect at the 2nd hour of the highest dose. Dihydro-cinnamic acid and cinnamic acid epoxide with 4mg/kg dose produced 55.5% and 54.9% inhibition of inflammation respectively at the second hour, while para-methoxy-cinnamic acid at the second hour with 2 mg/kg dose level produced 54.0% inhibition. The reference compound; diclofenac produced no significant inhibition of inflammation at 4mg/kg dose level. All the compounds showed mild antimicrobial activities against the tested organisms. Conclusion: The findings from the study indicate that the synthesized compounds possess mild anti-inflammatory, with weak antibacterial and antifungal activities.